16. Influence of the Calypso system on kV-CBCT's image quality and photon beams dose delivery. (December 2017) - Eustache, P.; Prunaretty, J.; Ailleres, N.; Fenoglietto, P.
Abstract : Introduction: The Calypso 4D Localization System uses electromagnetic detection of implanted transponders to continuously track treated targets[1, 2] . This system requires the introduction of an electromagnetic array in the treatment beam. The aim of this study was first to investigate the influence of the array on the kV-CBCT image quality and to evaluate its dosimetric impact on VMAT prostatic treatments. Methods: For the image quality evaluation part, kV-CBCT images of a CAPTHAN 500 were acquired using pelvic mode (120 kV and 80 mA) with and without the array. They were analyzed on the CTP-401 module. A region of interest (ROI) was traced on each target (air (x2), polystyrene, Low Density Polyethylene, Polymethylpentene, Teflon, Delrin and acrylic). Signal and standard deviation (SD) were measured on those 8 ROIs on 10 contiguous slices. Mean between the 8 ROIs for each slice was calculated. Signal and SD of the background were also evaluated. Wilcoxon matched pairs tests were used to study the influence of the array on the signal, the noise, the signal to noise ratio (SNR), the absolute contrast and contrast to noise ratio (CNR). Finally the correlation between the density and the difference of SNR between images was investigated. For the dosimetric evaluation, dose distributions were recalculated in a cylindrical phantom for 20 VMAT prostatic treatments (10 with 6 MV FF and 10 with 6 MV FFF beams). The dose prediction at the isocenter was compared to 0.125 cc ionization chamber measurements. Differences between measured doses with and without the array were calculated and averaged for each beam energy. Results: Regarding image quality, no signal differences were observed between both images, but there was a significant increase of noise (p < 0.01) within the image acquired with the array in place, resulting in a significant decrease in SNR (p < 0.01). This loss in SNR was positively correlated (p < 0.05, R2 = 0.699) with increasing density of the target. No differences in absolute contrast were observed. Finally, there was a significant decrease in CNR was (p < 0.01) even if the deviation was only of 2.5%. Regarding dosimetric evaluation, the mean dose was reduced by 0.61% (maximum: 0.80%) for 6 MV and by 0.31% (maximum: 0.86%) for 6 MV FFF beams when using the electromagnetic array. Conclusions: The Calypso system significantly increases the noise within kV-CBCT images, without degrading the absolute contrast. The impact on the patient positioning should be limited. Finally the dosimetric influence of the array may be considered negligible (<2%). This result is in accordance with another study[3] .